2022
DOI: 10.3390/nano12193517
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR Targeted Multifunctional I-131 Radio-Nanotherapeutic for Treating Osteosarcoma: In Vitro 3D Tumor Spheroid Model

Abstract: The systemic delivery of doxorubicin (DOX) to treat osteosarcoma requires an adequate drug concentration to be effective, but in doing so, it raises the risk of increasing organ off-target toxicity and developing drug resistance. Herein, this study reveals a multiple therapeutic nanocarrier delivery platform that overcomes off-target toxicity by providing good specificity and imparting enhanced tumor penetration in a three-dimensional (3D) human MG-63 spheroid model. By synthesizing PEG-PLGA nanoparticles by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…The full search is illustrated in the PRISMA flowchart ( Figure 2 ) . Finally, 70 studies fulfilling the inclusion/exclusion criteria were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 6...…”
Section: Resultsmentioning
confidence: 99%
“…The full search is illustrated in the PRISMA flowchart ( Figure 2 ) . Finally, 70 studies fulfilling the inclusion/exclusion criteria were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 6...…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lee et al [ 31 ] found that gefitinib at concentrations of up to 20 μM did not reduce the viability of several other osteosarcoma cell lines, confirming their robust resistance to gefitinib. Recently, Marshall et al [ 36 ], in order to value EGFR expression as a target in osteosarcoma, designed a complex nanoparticle that was able to deliver doxorubicin (a DNA-damaging agent) using a conjugated EGFR antibody. ZR2002 without encapsulation targets EGFR, damages DNA and exhibits superior cytotoxicity when compared with all the drugs in all cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…This intriguing finding revealed a paradoxical relationship between tumor elimination and bone regeneration, thus contributing to the development of more effective therapeutic strategies for OS [ 52 ]. In a separate study, Marshall et al put forth a nanocarrier delivery platform with improved tumor specificity and penetration in a 3D human MG-63 spheroid model [ 56 ]. They employed the double emulsion method to synthesize PEG-PLGA nanoparticles, encapsulating DOX and Na 131 I within the inner core [ 56 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
“…In a separate study, Marshall et al put forth a nanocarrier delivery platform with improved tumor specificity and penetration in a 3D human MG-63 spheroid model [ 56 ]. They employed the double emulsion method to synthesize PEG-PLGA nanoparticles, encapsulating DOX and Na 131 I within the inner core [ 56 ]. These were further conjugated with an epidermal growth factor receptor (EGFR) antibody for targeted delivery to human MG-63 cells [ 56 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
See 1 more Smart Citation